Observation of events with an isolated high energy lepton and missing transverse momentum at HERA - Adloff, C; Anderson, M; Andreev, V; Andrieu, B; Arkadov, V; Arndt, C; Ayyaz, I; Babaev, A; Bahr, J; Ban, J; Baranov, P; Barrelet, E; et al. (1998)
A search for events with an imbalance in transverse momentum and with isolated high energy leptons has been carried out at the positron-proton collider HERA. One event with an e- and five events with a μ± are found together with evidence for undetected particles carrying transverse momentum. Within the Standard Model the dominant origin of events with this kind of topology is the production of W bosons with subsequent leptonic decay. Three of the six events are within measurement errors found in a region of phase space likely to be populated by this process, while the remaining events show kinematic properties which are atypical of all Standard Model processes considered.